Sistem Informasi Pembayaran Uang Komite Berbasis Web Dengan Pemberitahuan WhatSapp Otomatis Di SMAN 11 Bulukumba - Dian Fadillah; Adi Candra; Auliya Rukmana Amar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
An information system integrates humans, hardware, software, and data to process information and support administrative activities and decision-making effectively. This study aims to: (1) design and develop a Web-Based Committee Fee Payment Information System with Automatic WhatsApp Notifications at SMAN 11 Bulukumba; and (2) determine user responses to the developed system. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The results indicate that the system successfully facilitates committee fee payment management and automatically delivers payment information to parents or guardians through WhatsApp notifications. User evaluation showed a score of 88.12%, categorized as Very Good, indicating that the system is well accepted and suitable for use at SMAN 11 Bulukumba.